0
$\begingroup$

Let's say that $$\ g(x) = \int_{2x}^{3x} \frac{(u^2-1)}{(u^2+1)} du$$

The question asks to find the derivative using FTC. I had two approaches to this problem, but one of them is missing a factor... let me explain:

My first approach:

$$ g'(x)=\frac{d}{dx} \left(\int_{2x}^{3x} \frac{(u^2-1)}{(u^2+1)}\right) = \frac{d}{dx} [ g(3x) - g(2x) ] = f(3x) - f(2x) $$

Plugging in arguments $3x$ and $2x$ in the integrand yielded $\frac{(9x^2-1)}{(9x^2+1)} - \frac{(4x^2-1)}{(4x^2+1)}$ . However, it is missing a factor of 3 in the first term and a factor of 2 in the second. I'm aware that these values come from the derivatives of the upper and lower limits respectively, but why didn't they show up?

My second approach was correct, however:

$$ \int_{2x}^{3x} = \int_0^{3x} - \int_0^{2x}$$ I'll just show the work for $\int_0^{3x}$...

therefore $\frac{d}{dx}3x=3$

$$ g'(x)=\frac{d}{dx} \left(\int_{2x}^{3x} \frac{(u^2-1)}{(u^2+1)}\right) = g'(x)=\frac{d}{db} \left(\int_{2x}^{3x} \frac{(u^2-1)}{(u^2+1)}\right) \frac{d}{dx}3x = 3\frac{(u^2-1)}{(u^2+1)}$$

As you can see, in this approach, the factor of 3 shows up because there is $\frac{d}{dx}3x=3$

Where does approach one go wrong?

$\endgroup$
  • $\begingroup$ If you enclose the upper/lower limits with {}, Mathjax will render the properly, i.e. \int_{2x}^{3x} f(t) dt will produce $$\int_{2x}^{3x} f(t) dt$$ $\endgroup$ – Pragabhava Dec 6 '12 at 6:40
1
$\begingroup$

Let $$g(x)=\int_{\alpha(x)}^{\beta(x)} f(t) dt.$$ By FTC, $$ g(x) = F(\beta(x)) - F(\alpha(x)) $$ where $F$ is an anti-derivative of $f$. Then by chain rule \begin{align*}g'(x) &= (F(\beta(x)))' - (F(\alpha(x)))' \\ &= f(\beta(x))\beta'(x) - f(\alpha(x))\alpha'(x). \end{align*}

In your case, $\beta'$ and $\alpha'$ give you the factors $3$ and $2$ respectively.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.